Valorization of polysaccharides using alternative solvents - Morais, Eduarda Serra (2022)
Sustainable development is one of the major concerns of society and of the scientific community presently. These concerns have led to new legislation by the European Union and United Nations focusing on the development of sustainable processes, mostly using greener solvents and renewable feedstocks as well as the implementation of a circular economy. In this sense, it is predicted that the share of bio-based chemicals will exponentially increase in the coming years through the valorization of biomass resources. Moreover, waste management is also a crucial point to achieve Circular Economy. Biomass represents thus a promising source for chemicals and materials. Nonetheless, the use of this feedstock must be carefully planned to be sustainable. To achieve a sustainable exploitation of biomass the use of biorefineries is key. Biorefineries are integrated systems of sustainable technologies for the comprehensive utilization and exploitation of biological raw materials. From the various types of available biomass, lignocellulosic feedstocks present the highest abundance with large quantities of the feedstock being wasted in pulp and paper manufacture and agro-based processes. This feedstock is however very complex, being composed of three main fractions: cellulose, hemicelluloses and lignin. The first two fractions are polysaccharides which can be used to produce new and innovative materials, chemicals and biofuels. Even so, there is a need for more efficient and sustainable use of these biomass fractions. Having these issues in mind, the main aim of this thesis is to explore the valorization of polysaccharides using alternative solvents, such as deep eutectic solvents (DES). The major fraction of the work was focused on the valorization of xylans which compose the majority of hemicelluloses fraction in lignocellulosic biomass. The initial work focused on the dissolution and extraction of these polysaccharides. In this study, the DES [Ch]Cl:Urea was able to solubilize a maximum of 328.23 g/L of xylans using 66.7 wt.% DES in water at 80°C. Moreover, xylans could be recovered easily from the DES by precipitation with yields above 90% while maintaining their main structural features intact. This DES also demonstrated the capability to selectively extract xylans from E. globulus wood which is key for a possible application in a biorefinery context. The next studies focused on the production of chemicals directly from this xylan, namely xylitol and furfural. Xylitol production was achieved through the simultaneous saccharification and fermentation of the xylans dissolved in the previous developed DES system, taking advantage of the mild extraction conditions to achieve a one step process. In this study, 66.04% of xylitol yield was attained using an aqueous solution of 20 wt.% of [Ch]Cl:Urea in the molar ratio of 1:1. Furfural production was explored focusing also on a one-step process. This was achieved through the design of a dual function DES, having the role of both solvent and catalyst. Through the use of the [Ch]Cl:Malic Acid (1:3) with 5 wt.% of water a novel and faster process was developed for furfural production. Moreover, the use of the bio-based solvent γ-valerolactone (GVL) allowed for a maximum furfural yield of 75% with 2.5 min of reaction time using microwave-assisted reactions, at 150 °C, at a S/L ratio of 0.050, and GVL at a weight ratio of 1:2 with the DES system. Furfural was also recovered after production through the use of the bio-based solvent 2-methyltetrahydrofuran (2-MeTHF) and the DES was re-used achieving a fully developed process. Then, the use of alkali metal salts was evaluated in the previous DES system composed of [Ch]Cl:Malic acid (1:3), and it was found that the use of these salts could highly influence the furfural yields attained. The use of LiBr allowed for a sharp increase in furfural yields without the need of GVL. A maximum furfural yield of 89.46% was achieved using 8.19% of LiBr in [Ch]Cl:Mal, 1:3; 5 wt.% water, at 157.3 °C and 1.74 min of reaction time. The final study regarding furfural production focused on the use of acidic-based aqueous biphasic systems (AcABS) for the simultaneous furfural production and separation. The aqueous biphasis system used was composed of the ionic liquid (IL) tributyltetradecylphosphonium chloride ([P444(14)]Cl) and hydrochloric acid (HCl), the latter acting both as a catalyst and phase-forming agent. Though the optimization of this process using microwave-assisted reactions, a maximum furfural yield of 78.8% and an extraction efficiency to the IL-rich phase of 85.5% were attained in 1 min in the microwave reactor, at 140 °C and 0.05 S/L ratio, with the ABS formed by 30 wt.% IL and 6.5 wt.% HCl. The use of this ABS also allowed for an easy re-use of the IL and recovery of furfural. The next study approached in this project had the goal of evaluating the feasibility of DES systems proposed in literature for biorefinery purposes, such as biomass delignification. When proposing these types of systems, to be used in whole biomass, it is crucial to understand the effect of the solvent and process on all the biomass fractions. Therefore, a comprehensive analysis was made to the DES system composed of [Ch]Cl:Lactic acid (1:10) proposed in literature for biomass delignification and its effect on the carbohydrate fractions. This study showed that esterification of cellulose occurs and that xylans are hydrolyzed into xylose and dehydrated into furfural, especially for higher treatment times. The last process approached in this thesis was focused on the production of 5-hyroxymethilfurfural (5-HMF), a valuable platform chemical. Herein, and similarly to the production of furfural in a one-step process, the acidic DES [Ch]Cl:Citric acid was used in the molar ratio of 1:1 to produce 5-HMF from fructose. The best 5-HMF yield attained after optimization was 82.4 % and was achieved at 130°C, in 4 min of reaction time with microwave, and with the addition of 10 wt.% of GVL. The recycling of the solvent and product recovery was carried out in a similar fashion revealing the versatility of the developed recovery process for a large array of furan compounds. In sum, this thesis demonstrates the potential of alternative solvents in the valorization of polysaccharide feeds. The different developed processes present a sustainable and more efficient alternative to the conventional processes in place, thus representing an important step in the paradigm shift to a circular economy and a more sustainable and holistic exploitation of biomass.